Nano-Archives in Soils—What Microbial DNA Molecules Can Report About the History of Places - Johann Michael Köhler (Applied Nano)
DNA encoding the 16S rRNA of bacteria is a type of nanometer-sized information storage that can be used to characterize bacterial communities in soils. Reading this molecular ’nano-archive’ is not only of interest for characterizing recent local ecological conditions but can also provide valuable information about human impacts on soils in the past. This is of great interest for archaeology and for understanding the ecological consequences of past human activities on recent ecological conditions. Powerful sequencing methods such as the Illumina process allow many different DNA sequences to be determined in parallel and provide very efficient data sets that reflect the composition of soil bacterial communities in topsoil layers as well as in translocated and covered soils of archaeological sites such as settlements, burials or workplaces. Here, a brief overview of recent developments in the use of these molecular nano-archives for the study of archaeological soil samples is given using typical examples.